Characterization and functional analysis of AhGPAT9 gene involved in lipid synthesis in peanut (Arachis hypogaea L.) - Shen, Yue; Shen, Yi; Liu, Yonghui; Bai, Yang; Liang, Man; Zhang, Xuyao; Chen, Zhide (Frontiers in Plant Science, 2023)
GPAT enzymes (glycerol-3-phosphate 1-O-acyltransferase, EC 2.3.1.15) catalyze the initial and rate-limiting step of plant glycerolipid biosynthesis for membrane homeostasis and lipid accumulation, yet little research has been done on peanuts. By reverse genetics and bioinformatics analyses, we have characterized an AhGPAT9 isozyme, of which the homologous product is isolated from cultivated peanut. QRT-PCR assay revealed a spatio-temporal expression pattern that the transcripts of AhGPAT9 accumulating in various peanut tissues are highly expressed during seed development, followed by leaves. Green fluorescent protein tagging of AhGPAT9 confirmed its subcellular accumulation in the endoplasmic reticulum. Compared with the wild type control, overexpressed AhGPAT9 delayed the bolting stage of transgenic Arabidopsis, reduced the number of siliques, and increased the seed weight as well as seed area, suggesting the possibility of participating in plant growth and development. Meanwhile, the mean seed oil content from five overexpression lines increased by about 18.73%. The two lines with the largest increases in seed oil content showed a decrease in palmitic acid (C16:0) and eicosenic acid (C20:1) by 17.35% and 8.33%, respectively, and an increase in linolenic acid (C18:3) and eicosatrienoic acid (C20:3) by 14.91% and 15.94%, respectively. In addition, overexpressed AhGPAT9 had no significant effect on leaf lipid content of transgenic plants. Taken together, these results suggest that AhGPAT9 is critical for the biosynthesis of storage lipids, which contributes to the goal of modifying peanut seeds for improved oil content and fatty acid composition.